2023
DOI: 10.1590/s1984-29612023010
|View full text |Cite
|
Sign up to set email alerts
|

Giardiasis in children and dogs, and the first report of assemblage E in dogs from northeastern Brazil

Abstract: Diagnosis is crucial for controlling giardiasis. We determined the prevalence and genetically characterize isolates of Giardia duodenalis of children and dogs from rural communities in northeastern Brazil. G. duodenalis cysts were concentrated by centrifugal flotation/sedimentation. Molecular characterization was carried out using the loci ssu-rRNA, bg, tpi, and gdh. By parasitological techniques, Giardia spp. infection was detected in 72/192 children (37.5%; 95% CI: 30.6%-44.7%) and 24/139 dogs (17.3%; 95% CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
2
0
1
Order By: Relevance
“…1). Den verschiedenen Assemblages können bevorzugte Wirte zugeteilt werden, jedoch gibt es keine obligatorische Wirtsspezifität [16][17][18]. Assemblages A und B bergen das höchste zoonotische Potenzial und haben die größte Bandbreite an Wirten.…”
Section: Taxonomieunclassified
“…1). Den verschiedenen Assemblages können bevorzugte Wirte zugeteilt werden, jedoch gibt es keine obligatorische Wirtsspezifität [16][17][18]. Assemblages A und B bergen das höchste zoonotische Potenzial und haben die größte Bandbreite an Wirten.…”
Section: Taxonomieunclassified
“…As with Cryptosporidium , several studies have suggested possible transmission of Giardia from pets to owners ( Traub et al, 2004 ; Palmer et al, 2008b ; Marangi et al, 2010 ; Quadros et al, 2016 ; Rehbein et al, 2019 ; Kuthyar et al, 2021 ; Harvey et al, 2023 ; Khalifa et al, 2023 ), particularly in socially-deprived areas. For example, in a low socioeconomic community in southern Italy, sub-assemblage AI was identified in nine of 14 dogs and six of 14 children ( Marangi et al, 2010 ).…”
Section: Zoonotic Risk Of Cryptosporidiosis and Giardiasis From Cats ...mentioning
confidence: 99%
“…In Argentina, assemblage A was detected in 12 humans and five pet dogs ( Kuthyar et al, 2021 ). In one study in Brazil, assemblage E was the only assemblage detected in dogs, and assemblages A, B and E were recovered from children from the same rural community ( Harvey et al, 2023 ). Another study of Giardia -positive samples from humans, dogs and cats in Brazil, identified assemblage F in one human and assemblages C, D and F in dogs and F in one cat ( Silva et al, 2022 ).…”
Section: Zoonotic Risk Of Cryptosporidiosis and Giardiasis From Cats ...mentioning
confidence: 99%